PENGARUH PELATIHAN FORMAL DAN KOMPENSASI TERHADAP KINERJA GURU DENGAN MOTIVASI INTRINSIK SEBAGAI VARIABEL INTERVENING (Studi Kasus pada Yayasan Pendidikan Informatika Serang) - Adiwinata, Djaka; Triadji, Bambang; Kuswantoro, M. (Faculty of Economics and Business - Universitas Sultan Ageng Tirtaysa, 2018)
Teacher role in challenges organization and reaching its objectives can happen when education teacher speaks apply what has gathered in training to students, the compensation, and motivation to excel. This study aims to see if formal training and compensation to depend on the intrinsic motivation and performance teacher at Yayasan Pendidikan Informatika. In this research, the methodology used is research causality. To answer the hypothesis using data analysis Structural Equation Model (SEM) using PLS (Partial Least Square). Based on the results of testing SEM obtained formal training have had a positive impact and significant impact on motivation intrinsic teachers, compensation influential positive and significantly to motivation intrinsic teachers, formal training has a positive and significant impact on teacher performance, compensation it has some positive effects and significantly correlates with is placed on teacher performance, Intrinsic motivation has a positive and significant effect on teacher performance.